БЎЛАЖАК ЎҚИТУВЧИЛАРДА ИЖТИМОИЙ КОМПЕТЕНТЛИКНИ ШАКЛЛАНТИРИШ ЙЎЛЛАРИ (Scientific journal of the Fergana State University, 2023)
The article considers the social competence of an educator as one of the main components of his/her professional activity. The educator social competence components, their essential characteristics, levels and stages of development had been analyzed.